Photopolymerization of Ceramic Resins by Stereolithography Process: A Review - Alessandro Bove; Flaviana Calignano; Manuela Galati; Luca Iuliano (Applied Sciences, 2022)
Stereolithography is known as one of the best Additive Manufacturing technologies in terms of geometrical and dimensional precision for polymeric materials. In recent years, a lot of studies have shown that the creation of ceramic resins, through a particular combination of monomeric components and ceramic powders, allows to obtain complex shape geometries thanks to the photopolymerization process. This review highlights the characteristics and properties of ceramic resins, peculiarities of the ceramic stereolithography processes, up to the relationship between the composition of the ceramic resin and the complexity of the post-processing phases. The comparison of different studies allows outlining the most common steps for the production of ceramic resins, as well as the physical and chemical compatibility of the different compounds that must be studied for the good feasibility of the process.